2022
DOI: 10.1007/s00401-022-02461-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of prion protein filaments from Gerstmann–Sträussler–Scheinker disease

Abstract: Prion protein (PrP) aggregation and formation of PrP amyloid (APrP) are central events in the pathogenesis of prion diseases. In the dominantly inherited prion protein amyloidosis known as Gerstmann–Sträussler–Scheinker (GSS) disease, plaques made of PrP amyloid are present throughout the brain. The c.593t > c mutation in the prion protein gene (PRNP) results in a phenylalanine to serine amino acid substitution at PrP residue 198 (F198S) and causes the most severe amyloidosis among GSS variants. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 65 publications
(112 reference statements)
1
43
0
Order By: Relevance
“…Our a22L structure allows us to provide high-resolution structural evidence for the long-proposed hypothesis that prion strains from a given type of host differ in conformation (913). This structure also adds to the short list of brain-derived pathological prions (5-7, 25-27) and PrP amyloids (28) that have PIRIBS-based fibril architectures, as we had predicted some years ago based on our observations of PIRIBS backbones in PrP Sc -seeded synthetic PrP fibrils (38). The highly infectious prion structures also share several key structural motifs, but the conformational details of these motifs vary between strains, even when the fibrils are assembled from monomers of the same PrP amino acid sequence.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our a22L structure allows us to provide high-resolution structural evidence for the long-proposed hypothesis that prion strains from a given type of host differ in conformation (913). This structure also adds to the short list of brain-derived pathological prions (5-7, 25-27) and PrP amyloids (28) that have PIRIBS-based fibril architectures, as we had predicted some years ago based on our observations of PIRIBS backbones in PrP Sc -seeded synthetic PrP fibrils (38). The highly infectious prion structures also share several key structural motifs, but the conformational details of these motifs vary between strains, even when the fibrils are assembled from monomers of the same PrP amino acid sequence.…”
Section: Discussionsupporting
confidence: 52%
“…Although non-fibrillar or sub-fibrillar ultrastructures can accompany amyloid fibrils in infectious brain-derived preparations of prions, all of the high-resolution structures reported to date (n=5, including a22L described herein) are fibrils with PIRIBS architectures (57, 25–27). A much less, if at all, infectious human GSS F198S-associated brain-derived PrP amyloid structure also has a PIRIBS architecture, but with a much smaller order core spanning residues 80-141 (62 residues) (28). As noted above, the much larger cores (132-138 residues) of the highly infectious prion structures extend nearly to the C-terminus and share several structural motifs; these include an N-proximal steric zipper, N, middle, and disulfide β-arches, and a central, and often staggered interface between N-and C-terminal lobes (57, 25–27).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reasoned that the delay of age at onset seen in heterozygous GSS(F198S) patients might be due to the inefficient aggregation of the endogenous M129 PrP because the bulky side chain of M129 does not fit the narrow space of the core. 23 It is intriguing that every PrP Sc whose structure was identified thus far has a Greek-key motif in the same region. This could imply the significance of a U-shaped loop in this region for PrP C –PrP Sc conversion.…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 22 In 2022, Hallinan et al reported cryo-EM structures of human PrP Sc isolated from the brains of patients with Gerstmann–Sträussler–Scheinker syndrome (GSS) associated with F198S mutation. 23 …”
Section: Introductionmentioning
confidence: 99%
“…The structural conversion of the α-helical folded cellular prion protein (PrP C ) into its pathological form, PrP Sc , causes TSE [ 11 ]. The very recently solved cryo-electron microscopy (EM) near-atomic structures of infectious, brain-derived PrP Sc fibrils unveiled a continuum of β-strand serpentine threading of the protein C-terminal domain and following studies have confirmed that the PrP Sc amyloids feature parallel in-register β-strand stack folding [ 12 , 13 , 14 , 15 , 16 , 17 ]. However, the conformational conversion of PrP C into PrP Sc appears as a multi-step process whose molecular mechanisms still remain unclear and are extremely difficult to probe at the single-molecule level.…”
Section: Introductionmentioning
confidence: 99%